2014
DOI: 10.1182/blood-2013-11-540781
|View full text |Cite
|
Sign up to set email alerts
|

B-cell tolerance regulates production of antibodies causing heparin-induced thrombocytopenia

Abstract: Key Points B-cell tolerance plays a critical role in controlling production of PF4/heparin-specific antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 23 publications
2
49
0
3
Order By: Relevance
“…26 To explain this atypical response, previous studies have proposed that the pattern of antibody formation might be more compatible with a non-T cell-dependent immune reaction, which is induced efficiently when an antigen is presented in a repetitive rigid form. 5,[27][28][29] The antigenic PF4/heparin complex can expose such repetitive epitopes, which are similar to repetitive viral epitopes known to cause T cell-independent B-cell activation. 5,30 A recent study of anti-PF4/heparin immunization in patients after cardiac surgery suggested that perioperative inflammation affects the immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 To explain this atypical response, previous studies have proposed that the pattern of antibody formation might be more compatible with a non-T cell-dependent immune reaction, which is induced efficiently when an antigen is presented in a repetitive rigid form. 5,[27][28][29] The antigenic PF4/heparin complex can expose such repetitive epitopes, which are similar to repetitive viral epitopes known to cause T cell-independent B-cell activation. 5,30 A recent study of anti-PF4/heparin immunization in patients after cardiac surgery suggested that perioperative inflammation affects the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…31 An inflammatory stimulus can break down PF4/heparin-specific B-cell tolerance, resulting in spontaneous production of PF4/heparin-specific antibodies, especially IgG antibodies. 5,28 DMT-associated inflammation may modify the immune system as an additional danger signal to trigger B cells, probably primitive marginal zone B cells, 29,32 with specificity for PF4/polyanion complexes. In the present study, the proportion of patients with high OD values ($1.4 units) appears to be higher in patients treated with any anticoagulant plus DMT than in patients treated with any anticoagulant but no DMT, although a significant difference was observed between TKA patients treated with and without DMT only when no anticoagulant was administered (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…These complexes are more common with UFH than LMWH and can trigger pre-existing PF4/heparin-intolerant B cells [59]. The chances of a B cell reaction leading to proliferation and antibody production may increase in some patients with repeated exposure to exogenous UFH, leading to a condition called heparin-induced thrombocytopenia (HIT).…”
Section: Heparin-induced Thrombocytopeniamentioning
confidence: 99%
“…Auto-reactive B-cells with anti-PF4 specificity were found in healthy mice and humans [16], suggesting that inflammation, surgery, and/or infection may breach selftolerance and lead to proliferation of auto-reactive B-cells and PF4-heparin antibody production. Recently, it has been shown that monocytes take up PF4-heparin complexes by an active endocytic pathway and then transport them to late endosomes, where the complexes still express the antigen recognized by HIT antibodies [17].…”
Section: Pathogenesismentioning
confidence: 99%